Fermentação lática da pimenta de cheiro (Capsicum chinense) para produção de picles probiótico - Souza, Karoline Lobo de (2017)
Pepper is one of the most consumed spices in the world, and the smell pepper is very appreciated for not presenting ardence and for being of pungent and distinguished aroma. It presents a wide variety of antioxidant compounds, and the taste, odor, texture and nutritional value, constitute attributes of quality to its commercialization. The objective of the study was to carry out the lactic acid fermentation of smell pepper (Capsicum chinense) from the inoculation of Lactobacillus plantarum R1012 to produce pickles with probiotic potential under the influence of glucose concentration (0.5, 1 and 2%) and NaCl (4, 5 and 6%). The vegetable subjected to the bleaching process was fermented at 20ºC for 72 hours and after the fermentation it was stored for 32 days at 4ºC. Its microbial growth and its pH were monitored during fermentation. Microbial counts and pH values revealed no differences between the brine samples as weel as the lactic acid bacteria counts in the pepper (> 9 Log CFU/mL) after fermentation. However, the best conditions for the preparation of the final product were 2% glucose, 6% NaCl and pH 6.5, presenting levels of 9.28 Log CFU/mL of lactic acid bacteria in the pepper, <10 CFU/mL of filamentous fungi and yeast, pH of 3.99 and titratable acidity of 0,18%. Throughout the storage, lactic bacteria remained at levels above 8 Log CFU /mL in pepper, fungi decreased, as did pH, due to the production of lactic acid. Therefore, the pickles are a viable product alternative for the introduction of functional ingredients such as probiotics.